RIGHT TO HEALTH IN INDIA - Satapathy, Ramakanta; Das, Bikram Kumar (International Multidisciplinary Research Journal, 2016)
Right to health is recognized by the constitution of India. The Constitution of World Health Organization states that, â€œHealth is a State of Complete physical, mental and social well being and not merely the absence of diseases or infirmity.â€ Right to health presupposes that, â€œ it is the duty of the State to raise the level of nutrition and standard of living of the people for good health. The apex court of India declared that Right to health is a fundamental right coming within Article 21 of the Indian Constitution. Right to health and health care needs multi-disciplinary services to monitor health condition of life. It is a huge task requires effective management and organized action.Â In this article an attempt is made to introspect the right to health within the constitutional parameters, international provisions and judicial decisions of Supreme Court. In this work doctrinal method is adopted to draw the conclusion.Â